Fabrication of Ionic‐Liquid‐Embedded ZnO Nanoparticles: Application of a Synergistic Catalytic Effect to Thiol‐Induced 2‐Pyridone Synthesis. Issue 5 (6th April 2018) - Mondal, Priya; Bhaumik, Asim; Chatterjee, Sauvik; Mukhopadhyay, Chhanda
Abstract: This is the first report of thiol‐induced, recyclable ZnO–[2COOHMIM] + Br − ‐catalysed (2COOHMIM=1‐(2‐carboxyethyl)‐3‐methylimidazolium), water‐mediated 2‐pyridone synthesis by two new straightforward strategies with 37 examples. This catalytic system was prepared using environmentally friendly, recyclable acidic‐ionic‐liquid‐coated ZnO nanoparticles (NPs). The changes in size and morphology upon capping the ZnO NPs were effectively tuned by neutral and acidic ionic liquids, which acted as structure‐directing mediators. ZnO has a high affinity for carboxyl functionalities, and accordingly, a 3D network was formed in which the carboxyl group acted as a linker. The catalysts generated by the capping of ZnO NPs with ionic liquids were characterised by scanning electron microscopy, transmission electron microscopy, dynamic light scattering, powder X‐ray diffraction, and FTIR spectroscopy. This combined catalytic system, containing both acidic and basic environments, exhibited properties of both a quasi‐heterogeneous catalyst and a phase‐transfer catalyst in aqueous medium. Here, a synergistic catalytic effect between ZnO NPs and acidic ionic liquids is utilised effectively. The recyclability of this catalytic system up to a fifth cycle was demonstrated by FTIR spectroscopy. Abstract : Working together : Two new straightforward strategies towards the synthesis of a library of biologically significant 2‐pyridone derivatives are reported. Both routes use recyclable ionic‐liquid‐embedded ZnO nanoparticles (ZnO–[2COOHMIM]Br, 2COOHMIM=1‐(2‐carboxyethyl)‐3‐methylimidazolium) with synergistic catalytic effect.